Using games in teaching grammar to young learners - Yang, Xueshuang; Alibar, Elida Alexander; Aralas, Dalia; Ismail, Lilliati; Othman, Moomala (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
Teaching grammar to young learners has been a challenging task especially among low to moderate proficiency L2 learners. Low vocabulary knowledge also contributes to the lower motivation in learning grammar. Thus, there are a few research studies shows that using games in teaching grammar is effective to young learners. This method does also help young learners to engage and integrate with the language. Studies also suggest that using games in teaching grammar will encourage, entertain and promote fluency of the young learners. This paper presents to further describe the different approaches used by the teachers on using games, the selection of games and the proper planning of using games in teaching grammar. Research findings suggest that games can also be used as another method to make the instruction helpful for the learners to understand, thus, giving a positive effect in creating a more interactive and creative environment among the learners. In addition, this present paper aims to look at how using grammar games can make the learning memorable, more communicative and promote collaboration among the L2 learners, unlike the teaching method that focuses on terminology and rules through skill-and-drill exercises.